To convert the given equation into vertex form, we need to complete the square.
First, let's group the terms:
y = x^2 + 6x - 9
Next, we want to add and subtract a constant inside the parentheses to complete the square. To determine the constant, take half of the coefficient of x and square it. In this case, half of 6 is 3, and 3 squared is 9.
y = x^2 + 6x + 9 - 9 - 9
Now, we can rewrite the equation as:
y = (x^2 + 6x + 9) - 9 - 9
Now, let's factor the square trinomial in the parentheses:
y = (x + 3)^2 - 18
Simplifying further, we have:
y = (x + 3)^2 - 18
Therefore, the correct vertex form of the equation is y = (x - 3)^2 - 4.
Select the correct vertex form of the following equation. show all your work
y=x2+6x−9
answer : y=(x−3)^2−4
1 answer